The use of indicators in the evaluation of retail planning: evidences from England - Guimarães, Pedro (2018)
Retail planning gained importance with the introduction of innovation in that sector, which challenged the vitality and viability of town centres. With this evolution and the arise of Town Centre First in England, the retail planning key documents started to incorporate indicators to help and standardize the monitoring of the health of town centres. This article aims to analyse the process of evaluation and verify the evolution of indicators suggested in the several public documents that constitute retail planning in England since 1993. It was based on the review of the main documents established in England since 1993. The research developed in this paper helps to update some information and is valuable for urban planners, practitioners and academics. In this paper we conclude that indicators are been used but without been framed in an evaluation framework and the variability of suggested indicators may have limited the analysis of the temporal evolution of town centres. In terms of research implications this paper helps to, in part, path the way for future research in this field.